The Influence of National Health Insurance Participant Satisfaction in Mediating the Relationship of Service Quality and Brand Image Towards Participant Loyalty at RSU Balimed Denpasar - Ni Kadek Diastuti; Ni Putu Cempaka Dharmadewi Atmaja; I Made Dauh Wijana; I Gede Cahyadi Putra (International Journal of Applied Business and International Management, 2024)
The irregularity of participants in paying National Health Insurance contributions shows that participants lack loyalty in paying contributions which are their routine obligations as participants in the National Health Insurance program. The aim of this research is to reveal the mediating impact of satisfaction on service quality and brand image on loyalty. This research is a quantitative research conducted using a survey, using data samples from National Health Insurance participants with active membership and receiving services at the Bali Med Denpasar General Hospital, totaling 82 people with PLS-based SEM analysis. The research results showed that service quality had a positive and significant effect on satisfaction, brand image had no significant effect on satisfaction, service quality and brand image had a positive and significant effect on loyalty, and patient satisfaction was able to mediate the effect of service quality and brand image on patient loyalty. It is hoped that the results of the research can provide advice to related parties to improve the quality of health services, such as how to respond to existing complaints and communicate well with patients and this is expected to have a positive impact on the quality of services.